UNSUR INTRINSIK DAN PERMASALAHAN SOSIAL DALAM CERPEN ULIAN LACUR KARYA NENGAH RUSMADI - I Wayan Nuryana (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2019)
Short story is one of literature in the form of prose. Short story is a work that is built through various intrinsic elements and extrinsic elements. Element element of the short story will build a short story in totality and is artistic. Short stories have intrinsic and extrinsic elements, intrinsic element is the element of the story builder that comes from within the short story itself. If likened to a building, then the intrinsic element is the components of the building. The intrinsic elements are themes, plot, figure, background, point of view and mandate. In addition to intrinsic elements also analyze the social value in this story which contains social problems such as poverty, faded empathy and so forth. As for the benefits of peeling a short story is very diverse, from the first did not know to know, who did not understand to understand, analyze / peel thoroughly a short story is very useful for writers and readers. Writers and readers will very easily understand the contents contained in a short story, especially for people who like to short stories.